Good agricultural practices for seed potato multiplication in Nigeria • Trainer Guide - International Potato Center (International Potato Center, 2023)
The sequence of modules and themes follows a certain logic as per the growth and development cycle of the potato crop. Therefore, it is recommended to follow the same sequence during training sessions. This guide can be used either for the training of trainers (the training of potential trainers of producers) or directly for the training of producers. For each theme, the trainer-of-trainers or the trainer should allocate a minimum of 15 minutes for presentation and 10 minutes for questions and answers. In total, the course requires a minimum of 8 hours to be completed, equivalent to a 2-day training workshop for the trainers or 4 training sessions of 2 hours for the producers. In a bid to gauge the impact made in training at any level, trainers are encouraged to assess participants’ knowledge through a written test before and after the training using the same questionnaire. A test sample is provided in appendices. It is recommended that the trainers pass an evaluation test with a score of at least 12/20.